Adolescents and the Prostitution Industry: Changing Patterns of Prostitution, Motivations, Assessments, and Risks Faced - Nugroho, Efa; Nisa, Alfiana Ainun; Hermawati, Bertakalswa; Raharjo, Bambang Budi; Kamka, Erry H; Saputri, Erina Slamet; Hermawan, Dwi Yunanto; Widyaningrum, Heny (Jurnal Kesehatan Masyarakat, 2025)
The phenomenon of adolescents involved in the prostitution industry was widespread globally, including in Indonesia. This study focused on the changing patterns of prostitution, motivations, perceptions, and risks faced by adolescent sex workers. The research used a mixed-method approach, employing both quantitative and qualitative designs. Data were collected through surveys involving adolescent sex workers and general adolescents, as well as in-depth interviews with adolescent sex workers. The quantitative study included 360 respondents, comprising 180 general adolescents and 180 adolescent sex workers, while the qualitative study involved 30 adolescent sex workers as informants. The research was conducted in Bali, South Kalimantan, West Java, North Sulawesi, North Sumatra, and Central Java provinces. The findings revealed a shift in prostitution patterns among adolescents from conventional (street-based) prostitution to online prostitution via digital platforms. Adolescents had greater opportunities to become online sex workers due to the diversity of social media platforms and service types available. Economic factors accounted for 81.7% of adolescents' reasons for becoming sex workers. There was a disparity in perceptions between general adolescents and the actual challenges faced by adolescent sex workers. Among adolescent sex workers, 80% had low reproductive health knowledge, 23% had experienced sexually transmitted infections (STIs), 16% had faced unwanted pregnancies, and 7% had undergone abortions. It was concluded that there were significant changes in the patterns, motivations, perceptions, and risks associated with adolescent sex work.